Risk Factors for Acute Respiratory Infections in Toddlers in Puskesmas Kuta Krueng Area, Pidie Jaya 2024 - Fitria, Nidaul; Fauzi Ali Amin; Hanifah Hasnur (Media Publikasi Promosi Kesehatan Indonesia (MPPKI), 2024)
Introduction: Aceh Province ranks third in Indonesia for acute respiratory infections (ARI), with a prevalence of 30.0%. Among its districts, Pidie Jaya has the highest ARI incidence at 7.84%, with Bandar Dua subdistrict reporting the highest number of cases. Toddlers are particularly vulnerable to ARI, which can significantly impact their growth and development. Objective: This study aims to explore the associations between nutritional status, exposure to cigarette smoke, exclusive breastfeeding, and maternal knowledge with the incidence of ARI in toddlers in the Puskesmas Kuta Krueng area, Bandar Dua subdistrict, Pidie Jaya district in 2024. Method: This quantitative study uses a descriptive case-control design to analyze the relationships between independent and dependent variables. The study population consists of 792 mothers with toddlers in the Puskesmas Kuta Krueng area, including 192 cases of ARI. The sample size, calculated using the Lemeshow formula, includes 96 cases and 96 controls, selected through proportional sampling. Result: Univariate analysis shows that 49.0% of toddlers have poor nutritional status, 33.3% are exposed to cigarette smoke, 29.7% did not receive exclusive breastfeeding, and 41.1% of mothers have inadequate knowledge. Bivariate analysis reveals significant associations between nutritional status (OR=9.014; p-value=0.000), exposure to cigarette smoke (OR=2.366; p-value=0.006), exclusive breastfeeding (OR=2.655; p-value=0.003), maternal knowledge (OR=2.097; p-value=0.013), and the incidence of ARI in toddlers. Conclusion: The study identifies poor nutritional status, exposure to cigarette smoke, lack of exclusive breastfeeding, and inadequate maternal knowledge as significant risk factors for ARI in toddlers. These findings suggest that targeted public health interventions are essential to improve nutritional status, reduce smoke exposure, promote exclusive breastfeeding, and enhance maternal education. Such measures could significantly lower ARI rates and improve overall toddler health outcomes. The study's limitations include its cross-sectional design and potential recall bias. Future research should focus on longitudinal studies and intervention strategies to address these issues more effectively.